Double salt ionic liquids prepared by mixing partially miscible ionic liquids: Tuning the solubility of lipophilic molecules - Wang, Hui (2014)
Double Salt Ionic Liquids (DSILs) were prepared by mixing 1- ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][NTf2]) and trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide ([P66614][NTf2]) in their miscible range: [C2mim]x[P66614](1-x)[NTf2] (0 ≤ x ≤ 0.29). 1H NMR, 19F NMR, and FT-IR spectroscopic studies indicated that the [NTf2]- anions preferentially interact with the [C2mim]+ cations. Solubility studies showed that solutes with long alkyl chains (e.g., heptane, methyl palmitate), which have good solubility in [P66614][NTf2] but are not totally miscible, have tunable solubility in the DSILs and the presence of even minor amounts of [C2mim]+ significantly decreases their solubility. However, the solubilities of benzene, toluene, 1-octanol, and poly(ethylene glycol) (PEG-300) in [C2mim]x[P66614](1-x)[NTf2] were controlled by their miscibility with [P66614][NTf2], and can't be tuned by changing the ion concentrations within the miscibility range.